Lifetime alcohol use patterns and risk of diabetes onset in the National Alcohol Survey - Kerr, William C. (Alcohol Clin Exp Res, 2018)
BACKGROUND: Studies of the role of alcohol use in diabetes risk have rarely included lifetime alcohol use measures, including the frequency of heavy occasions, or evaluated risks among Black or Hispanic respondents in US samples. METHODS: Data from the 2014–15 National Alcohol Survey of the U.S. population were used to estimate diabetes risk from drinking patterns at the time of onset in Cox proportional hazards models in a retrospective cohort design. Models for the population, males and females and for White, Black and Hispanic respondents of both genders were estimated using two versions of drinking pattern groupings at each age. RESULTS: While a number of significant results were found with the first version of the drinking measures, we focus on those confirmed with measures from responses strictly prior to the age of risk estimation. Compared to the lifetime abstainer group, the ‘drinking at least weekly with less than monthly 5+’ group had a significantly lower hazard ratio (HR) for the total sample (HR=0.64) and among Whites (HR=0.42). Significantly reduced risks were found in the same models for those who drank 5+ at least monthly but not weekly. No significantly elevated risks were found for either current or prior heavy occasion drinking. CONCLUSIONS: These results are consistent with some prior studies in finding reduced risks for regular light to moderate drinkers, but not consistent with findings from other studies showing increased risk from heavy occasion drinking, particularly among women. New and larger studies with well-defined drinking pattern measures are needed, particularly for US Blacks and Hispanics, to address varying results in this literature.